(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
The article provides information about information technology and computer mathematics systems. The advantages of Mathcad and Maple and how to use these programs to solve differential equations are explained in detail. In addition, the article contains several suggestions and recommendations for teachers of mathematics on the use of Mathcad and Maple in the educational process